PENGARUH REWARD TERHADAP KEPUASAN KERJA KARYAWAN PADA CV. AGUNG PUTRA JAYA MANDIRI KABUPATEN TABALONG - Septiyana Lestari; Saroyo (JAPB, 2022)
Reward is a form of appreciation given by the company for the achievements that have been made by employees because they can work beyond the standards set by the company. This reward is expected to motivate and increase the level of job satisfaction of each employee. The purpose of this study is 1) To determine the effect of rewards on employee job satisfaction at CV. Agung Putra Jaya Mandir, Tabalong Regency and 2) To find out how much influence the reward has on employee job satisfaction at CV. Agung Putra Jaya Mandiri, Tabalong Regency. This research is included in quantitative research, the sampling technique used in this research is using a saturated sampling technique with a total sample of 42 respondents assisted by the GSCA analysis tool. The results of the study concluded that 1) Reward has an effect on employee job satisfaction at CV. Agung Putra Jaya Mandiri, Tabalong Regency 2) The magnitude of the reward effect on employee job satisfaction at CV. Agung Putra Jaya Mandiri Tabalong Regency by 56.6% and 43.4% influenced by other variables. Keywords: Reward, Job Satisfaction, GSCA